PREPARATION, PHYSICAL-CHEMICAL CHARACTERIZATION AND SENSORY ANALYSIS OF A CREME FEITO WITH JAMBO FLOWERS (Syzygium malaccense L.) (International Seven Journal of Multidisciplinary, 2025)
Amazonia, located mainly in the North of Brazil, is a region with a wide and rich biodiversity, mainly in flora, presenting numerous fruit species, both exotic and native to the Amazon forest. Jambo (Syzygium malaccense) is an exotic species present in the Amazon, where its fruits are widely consumed by local populations. Still, its flowers, intended for human consumption, do not usually be used for food. This study sought to prepare a jambo flower cream, and characterize the physical-chemical point of view of such a product, in addition to carrying out a sensory analysis with untrained testers. The physical-chemical results suggest that the product is of good quality, not very acidic (pH = 6.61). On the other hand, a sensory analysis carried out revealed some jambo flower cream oil.